Live In sebagai Model Pengabdian kepada Masyarakat: Refleksi Kunjungan Pastoral dan Sosial dalam Asistensi Natal - Fransiskus Saverius Minggu; Yulianus Kian; Jefrianus Ulu Manek; Paskalis Jhon Juan; Frederikus Rifaldo Soro; Robertho Mario Wetan Kwure (Jurnal Pengabdian Masyarakat, 2026)
The Live-In / Pastoral and Social Visit activities in the context of Christmas Assistance are a form of community service carried out by students of the Institute of Philosophy and Creative Technology (IFTK) Ledalero at the Santo Matius Lewumbangga Parish Subdistrict. This activity aims to implement students’ academic knowledge, faith, and social concern through direct involvement in the life of the congregation, especially in welcoming and celebrating Christmas. The method of implementation is participatory and contextual, with activities including pastoral service, catechesis for parishioners and youth, guidance for SEKAMI, social service, communal work, liturgical service, visits to the sick and elderly, as well as educational activities in the school environment. The results of the activities show the building of closer relationships between students and the congregation, increased participation of the faithful in pastoral activities, and the growth of solidarity, togetherness, and social concern. For students, the Live-In activity becomes a means of contextual learning that enriches character formation, social sensitivity, and the appreciation of service values. This activity affirms that Live-In can be an effective model of community service that integrates faith, knowledge, and concrete action in a pastoral and social context.